The Effect of Financial Ratios on Financial Distress with Corporate Governance as a Moderation Variable in Tourism Industry Service Companies, Hotels and Restaurants Listed on the Indonesia Stock Exchange - Selpia Sapitri; Irdha Yusra (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to explore the impact of the influence of financial ratios on financial distress with corporate governance as a moderation variable in tourism industry, hotel and restaurant service companies listed on the Indonesia Stock Exchange during the 2019-2023 period. The method used in this study is purposive sampling from a total of 50 companies, where 23 companies were selected because they met the criteria that have been set. The analysis was carried out to involve multiple linear regression and moderating regression analysis (MRA) by utilizing the IBM SPSS Statistics 23 application as a tool for statistical and hypothesis testing. The financial distress variable was driven using the Zmijewski X-Score formula. The findings of the study show that return on equity (ROE) has a negative and significant influence on financial distress. Current ratio (CR) has a positive and significant influence on financial distress. Debt to equity ratio (DER) has a positive and insignificant effect on financial distress. In the moderation test, it can be seen that gender diversity does not positively moderate the effect of return on equity (ROE) on financial distress. Similarly, gender diversity does not positively moderate the influence of the current ratio (CR) on financial distress. However, gender diversity is able to negatively moderate/weaken the influence of debt to equity ratio (DER) on financial distress. Institutional ownership negatively moderates/weakens the effect of return on equity (ROE) on financial distress. However, institutional ownership does not negatively moderate the influence of the current ratio (CR) on financial distress. On the other hand, institutional ownership is able to positively moderate/strengthen the influence of the Debt to equity ratio (DER) on financial distress.